The 1968 Lamongan Flood: Solidarity Between the Government and Community in Facing Disaster - Alfina Dwi Septiani; Putri Agus Wijayati (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study discusses the Lamongan flood disaster in 1968, which was the largest disaster in the history of Lamongan Regency. This event had a huge impact on the people of Lamongan, both in terms of material and non-material losses. This study aims to determine the impacts and forms of cooperation between elements of society in dealing with the 1968 flood disaster. This study uses historical methods consisting of heuristics, criticism, interpretation, and historiography, supported by the availability of adequate primary sources through newspapers. The results of the study reveal that the floods that hit the Lamongan area demonstrated the resilience of the community through mutual cooperation, independent resource management, and seeking assistance from surrounding areas. These findings illustrate how social solidarity and community strength were the main factors that supported their resilience in the midst of extreme environmental pressures.